Health monitoring in the home of the future. - Korhonen, I.
We discuss health monitoring as a potential application field for wearable sensors. We present some usage models for health monitoring and discuss the technical requirements for the health-monitoring system based on wearable and ambient sensors, which measure health-related data in daily environments of the users or patients. The presentation is by no means complete, but it aims to give an idea of the system-level issues to be considered for real applications. The technology in this area is rapidly developing, and without doubt we will evidence emergence of these applications in the coming years in the market.
Keywords: Daily environments; Health monitoring; Home of the future; Rapidly developing technology; System-level issues; Usage models; Wearable sensors